Breve reseña histórica de la producción y cultivo del trigo (triticun sativum) en el desarrollo económico social y cultural de la parroquia de San Isidro - Imbaquingo Pulles, Margarita Lucía (2019)
SUMMARY San Isidro is a clearly agricultural and livestock parish since its foundation on April 23, 1898, people have deep roots in the feeling of belonging to the land and faith by their patron San Isidro Labrador. (specific objectives) When a few decades ago this land was very prosperous thanks to the cultivation of wheat, achieving with this important achievements at the level of collective and personal development by farmers who saw in the grain of gold the opportunity to grow economically, So much was the importance of this culture that the parish was considered the granary of the Carchi, in the frame of reference is with some key concepts as well as the great Christian faith is corroborated, which made the inhabitants feel the commitment to give back in something blessings that were receiving and parties were held in honor of the abundant wheat harvests that until 1999 merged with the parochialization of San Isidro, now every parade and float that decorate for any holiday is always present symbolically the image of the wheat next to the parish by its presence in the shield of the parroquia and together with their religious patron San Isidro Labrador who always carries with him an ear of wheat in his hand, applying the proposed methodology we can gather information with which we can „not deny that historically wheat is and will be very important in economic, cultural life and social of the parish of San Isidro, canton Espejo, province of Carchi. In the results it is determined that the influence of wheat cultivation in the economic, social and cultural history of the Parish of San Isidro, Cantón Espejo, Provincia del Carchi had a lot of weight that until today are still very important lags. Keywords: Wheat, culture, religion, information, economics, traditions, history, production.